Arthroscopic Modified Bosworth Procedure for Refractory Lateral Elbow Pain With Radiocapitellar Joint Snapping. Issue 6 (29th June 2020) - Jeon, In-Ho; Kwak, Jae-Man; Zhu, Bin; Sun, Yucheng; Kim, Hyojune; Koh, Kyoung-Hwan; Kholinne, Erica
Background: Radiocapitellar joint snapping due to the presence of synovial plica has been described as a contributory intra-articular pathology of lateral epicondylitis (LE). Hypothesis: The arthroscopic modified Bosworth technique can provide a safe and favorable outcome for refractory LE with radiocapitellar snapping. Study Design: Case series; Level of evidence, 4. Methods: Patients treated with the arthroscopic modified Bosworth procedure for refractory LE with radiocapitellar joint snapping were included in this study. The sequential surgical procedures included excision of the upper portion of the anterolateral annular ligament, removal of the synovial plicae, and release of the extensor carpi radialis brevis for all patients. Clinical outcomes were measured at a minimum 1-year follow-up. Results: A total of 22 patients with a mean ± SD age of 51.2 ± 10.4 years were included in this study. The mean follow-up was 29.4 ± 7.7 months (range, 21-42 months). The overall visual analog scale score (from preoperative to final follow-up) was 7.5 ± 1.2 vs 2.5 ± 1.8 ( P < .001); flexion-extension motion arc was 133.8° ± 11.2° vs 146.4° ± 7.1° ( P = .001); pronation-supination motion arc was 101.8° ± 9.2° vs 141.7° ± 10.2° ( P = .001); Disabilities of the Arm, Shoulder and Hand score was 54.5 ± 13.2 vs 3.6 ± 4.1 ( P < .001); and Mayo Elbow Performance Score was 51.9 ± 12.2 vs 84.3 ± 10.3 ( P < .001). Conclusion: Radiocapitellar joint snapping may coexist with LE as a disease spectrum. The arthroscopic modified Bosworth technique provides safe and favorable outcomes for patients with refractory LE associated with radiocapitellar joint snapping.